Pengaruh Pondok Pesantren Darussalam Al-Waliyyah Terhadap Ekonomi Masyarakat Desa Blang Poroh Kecamatan Labuhan Haji Barat, Aceh Selatan (1980-2020) - Aswira, Herdi; Ibrahim, Husaini (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The economic progress of a region in Indonesia is often caused by an institution, be it an educational institution or other institutions. The openness of an institution to the surrounding community greatly influences the community's economy. The study entitled "The Influence of the Darussalam Al-Waliyyah Islamic Boarding School on the Economy of the Blang Poroh Village Community, West Labuhan Haji District, South Aceh (1980-2020)" is to find out the conditions of the Blang Poroh Village community before the Darussalam Al-Waliyyah Islamic boarding school existed, and to find out what factors influenced the Blang Poroh Village community to switch livelihoods and to find out how the Darussalam Al-Waliyyah Islamic Boarding School influenced the economy of the Blang Poroh Village community, West Labuhan Haji District, South Aceh. This study uses a historical method with a qualitative approach and data collection techniques are carried out with the stages of field observation, interviews, documentation and literature studies. The results of this study describe that economic changes in the Blang Poroh Village community are caused by the openness of the Darussalam Al-Waliyyah Islamic boarding school to the community. Before the existence of the Islamic boarding school, the economy of the people of Blang Poroh Village still depended on the agricultural and marine sectors. Significant changes in the economy of the people of Blang Poroh Village occurred in 1980 which was in line with the development of the Islamic boarding school. The economic development of the people of Blang Poroh Village occurred in the trade sector so that many people changed their livelihoods and chose to trade. The economic progress that occurred in Blang Poroh Village can be seen from the number of shophouses in Blang Poroh Village reaching 50 shophouses and the number of entrepreneurs in Blang Poroh Village. From the results of this study, the existence of the Darussalam Al-Walliyah Islamic boarding school is very influential in advancing the economy of the people of Blang Poroh Village.